PENGARUH PENGGUNAAN MEDIA KARTU HURUF BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II SD NEGERI 7 AITINYO KABUPATEN MAYBRAT - Febelina Brin; Abdulrahman Hatsama; Desti Rahayu (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This type of research is Quantitative Research. This research aims to find out: (1) Letter Card Media applied by researchers to students; (2) Students' initial reading ability in all subjects. This research was carried out from 5 August to 14 September 2024, at SD Negeri 7 Aitinyo, Maybrat Regency. The method used in the research was the letter card method, namely looking at the form of relationship between the variables studied. The variables studied were letter card media and the beginning reading ability of second grade elementary school students. The research subjects were class II students at SD Negeri 7 Aitinyo, Maybrat Regency. The instrument used to obtain data was a questionnaire. Data processing from the questionnaire was carried out by analyzing product moment correlations according to the variables studied in the research, namely, parenting pattern variables (X) and students' initial reading ability (Y). The results of research using product moment correlation show that the calculated "r" value is -0.029, while the null hypothesis (Ho) is rejected. So it can be concluded that there is an influence on the use of letter card media and the initial reading ability of class II students at SD Negeri 7 Aitinyo, Maybrat Regency.